Program Sosialisasi Dan Aksi Pencegahan Covid-19 Pada Masyarakat Desa Jonggol Jambon Ponorogo - Yuniyanti, Risma Faizah; Ilma, Mughniatul (Dharma: Jurnal Pengabdian Masyarakat, 2022)
The emergence of the classification of the Corona Virus or Covid-19 which has spread to all parts of the world is no exception to the country of Indonesia which is also facing this problem, both provinces, capitals, and districts also feel the negative impact of the Corona virus. The virus is able to mutate into a new virus variant. Therefore, the author carried out a socialization program and preventive action against covid-19 and the purpose of the Community Service Lecture (KPM) activity was to help and provide socialization education or understanding of the importance of implementing health protocols in the covid-19 pandemic situation. It is hoped that with this program the community will be more aware and able to obey the health advice that has been recommended with a disciplined and responsible attitude. This activity uses 5 stages, namely through the ABCD (Asset, Based, Community Development) settlement method which has been used to invite community partners or youth in Jonggol Village, Jambon District, Ponorogo Regency to take advantage of the health potential they already have. The results that have been achieved from this community service are (1) increasing public knowledge and insight about the importance of complying with health protocols, (2) people have high awareness about the dangers of Covid-19, (3) people are able to implement a healthy lifestyle. The program is expected to be sustainable in the community and provide many benefits and can avoid the Covid-19 virus